2020
DOI: 10.1142/s0219843619500361
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Tactile Feedback for Biped Balance and Locomotion on Unknown Terrain

Abstract: This work introduces a new sensing system for biped robots based on plantar robot skin, which provides not only the resultant forces applied on the ankles but a precise shape of the pressure distribution in the sole together with other extra sensing modalities (temperature, pre-touch and acceleration). The information provided by the plantar robot skin can be used to compute the center of pressure and the ground reaction forces. This information also enables the online construction of the supporting polygon an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Wu et al [60] used a flexible capacitive sensor array on robotic feet to measure the tactile force distribution with the ground and adaptively adjust the gait. Guadarrama et al [61] studied tactile feedback control for a biped robot when it adapts to an unknown terrain. A research team at Massachusetts Institute of Technology (MIT) realized autonomous high‐speed bounding of Cheetah robots on a complex terrain using tactile intelligence [62].…”
Section: Embodied Tactile Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al [60] used a flexible capacitive sensor array on robotic feet to measure the tactile force distribution with the ground and adaptively adjust the gait. Guadarrama et al [61] studied tactile feedback control for a biped robot when it adapts to an unknown terrain. A research team at Massachusetts Institute of Technology (MIT) realized autonomous high‐speed bounding of Cheetah robots on a complex terrain using tactile intelligence [62].…”
Section: Embodied Tactile Sensingmentioning
confidence: 99%
“…(A) Reproduced with permission from Ref. [61], ©the authors, 2019. (B) Reproduced with permission from Ref.…”
Section: Embodied Tactile Sensingmentioning
confidence: 99%
“…In this study, we try to integrate rich tactile information, such as slippage, contact state, texture, and hardness, into a multimodal sensor for giving robots the ability to directly haptic sensing. G. Cheng et al reported a multimodal sensor integrating proximity, normal force, acceleration, and temperature for humanoid robots [ 19 ]. However, in-plane integration of different sensors leads to heterogeneity at different points and cuts off the connection between multimodal messages.…”
Section: Introductionmentioning
confidence: 99%
“…Tactile feedback is also an important means for human beings to perceive and interact with the environment. Equipped with tactile perception on robots, it not only simulates the mechanism of human perception and cognition, but also meets the strong demand for robot applications [2,4]. If the robot has, like a human, the ability to recognize and distinguish the surface texture of an object, it can improve the robot's working performance.…”
Section: Introductionmentioning
confidence: 99%